1995
DOI: 10.1063/1.469122
|View full text |Cite
|
Sign up to set email alerts
|

The equation of state of polyamorphic germania glass: A two-domain description of the viscoelastic response

Abstract: We have measured the quasistatic room temperature equation of state of GeO2 glass under hydrostatic conditions to 7.1 GPa. From ambient pressure to 4 GPa the compression displays completely reversible elastic behavior. Above 4 GPa the glass becomes anelastic and exhibits a dramatic increase in the static compressibility. This change in elastic response is concomitant with the onset of the previously reported pressure-induced germanium coordination change. The equation of state data can be quantitatively descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 39 publications
6
96
1
Order By: Relevance
“…The equation of state (EOS) of GeO 2 has been reported by different authors, either on the basis of simulations [119] or from empirical models based on simple structural arguments [132]. In the latter, Smith and co-workers have shown that a two state function, taking into account the effect of the tetrahedral and octahedral character at low and high pressures, is able to describe the experimental equation of state at 300 K, whereas molecular dynamics simulations only succeed in simulating the EOS in the low pressure range.…”
Section: Equation Of Statementioning
confidence: 99%
“…The equation of state (EOS) of GeO 2 has been reported by different authors, either on the basis of simulations [119] or from empirical models based on simple structural arguments [132]. In the latter, Smith and co-workers have shown that a two state function, taking into account the effect of the tetrahedral and octahedral character at low and high pressures, is able to describe the experimental equation of state at 300 K, whereas molecular dynamics simulations only succeed in simulating the EOS in the low pressure range.…”
Section: Equation Of Statementioning
confidence: 99%
“…This lies well above the observed crystallineamorphous transition pressure, which takes place at 16 GPa. However, we must recognize that the two-state EOS does not correspond to a fully relaxed material [Smith et al, 1995]. To estimate the order of magnitude of the correction which might be involved if the volume relaxation associated with the A1 coordination change occurred at lower pressure, we used the "high-temperature liquid" (~2100 K) points from Boslough et al…”
Section: Thermodynamics Of Anorthite At High Pressure Thermodynamics mentioning
confidence: 99%
“…Although compression measured by Smith et al 24 is greater under hydrostatic loading ͑HL͒, the trend in the data is the same. The bulk and longitudinal wave velocities of vitreous GeO 2 under hydrostatic loading increase slowly with increasing pressure when the pressure is below 4 GPa ͑Fig.…”
Section: A Vitreous Geo 2 Response To Planar Impactmentioning
confidence: 52%
“…Therefore, we conclude that the phase transition to rutile phase in vitreous GeO 2 starts at ϳ4 GPa and is completed in the pressure range of 14 to 16 GPa. Durben and Wolf 16 and Smith et al 24 also inferred that the four-to sixfold GeO 2 transition also occurred between 5.6 and 13 GPa under quasistatic loading.…”
Section: A Vitreous Geo 2 Response To Planar Impactmentioning
confidence: 99%
See 1 more Smart Citation